Functionalization of carbon nanotubes using eutectic mixtures: a promising route for enhanced aqueous dispersibility and electrochemical activity - Abo-Hamad, Ali; Hayyan, Maan; AlSaadi, Mohammed AbdulHakim; Mirghani, Mohamed Elwathig Saeed; Hashim, Mohd Ali (Elsevier, 2017)
Eutectic mixtures (EMs) were used for functionalization of carbon nanotubes (CNTs). The process consists of two main steps: a pretreatment with an acidic KMnO4 solution followed by an ultrasound treatment of CNT with the EM as a new class of environmentally-friendly solvents. Various ammonium and phosphonium based-EMs were used in the process and changes were recorded with respect to the functional groups on the CNT surface. Raman spectroscopy and X-ray diffraction analysis conﬁrmed successful cova- lent functionalization without substantial damage to the structure. Accurate characterization of CNT dispersions was also carried out using UV–Vis spectroscopy and zeta potential. Studying the dispersion behavior of CNTs in aqueous solutions showed that modiﬁed CNTs presented different dispersibility due to the changes in hydrophilicity after functionalization. The suspension stability of all modiﬁed- CNTs improved considerably compared to pristine CNT. Textural and structural characterization suggested an increase in surface area after functionalization due to exfoliation, open-ended tubes, and elimination of catalyst particles. EM-functionalized-CNTs were found applicable in electrochemical sensing. The electrochemical performance for one of the functionalized-CNTs was studied on the surface of a glassy carbon (GC) electrode for the detection of nitrite. Improved catalytic activity and sensitivity were obtained compared to bare and pristine CNT-modiﬁed GC electrodes with a detection limit of 1.35 lM.